Negative correlation between cardiometabolic index and testosterone in male adults - Xu, Jing; Li, Yue-Chun (Frontiers in Endocrinology, 2024)
Background: Insulin resistance (IR) is closely correlated with a deficiency or decrease of testosterone levels in males. Cardiometabolic index (CMI) is correlated with various diseases correlated with IR. The primary objective of this study is to explore the correlation between CMI and testosterone levels in male adults. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) during the period from 2013 to 2020 were analyzed through a cross-sectional design. CMI was calculated by multiplying waist-to-height ratio (WHtR) with the triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-C).Results: A total of 5012 subjects were included in the final analysis. After controlling confounding variables, multiple linear regression analysis indicated an independent negative correlation between CMI and testosterone levels (β= -6.40, 95% CI: -8.95, -3.86, P<0.001) through the. In addition, a negative non-linear correlation was also found between CMI and testosterone (P<0.05), with CMI's inflection point as 0.73. Subgroup analyses indicated a more significant negative correlation among those with normal weight and the elderly (p< 0.05 for all interactions). The area under the ROC curve (AUC) of CMI (AUC =0.724, 95% CI: 0.709-0.740) was the largest compared with those of TG/HDL and WHtR.Elevated CMI is significantly and negatively correlated with testosterone in male adults.